Toxicological Effects of Tobacco Compounds on the Expression of Genes Involved in Actinic Cheilitis - Thiago Cavalcanti Leal; Luiz Carlos dos Santos; Ana Kelly Fernandes Duarte; Gabriel Cerqueira Braz da Silva; Jéssica Alves Gomes; Valdemir da Conceição; Wellington Danilo Soares (Dentistry, 2017)
The molecular effects of substances present in tobacco and cancer development have been well described. Morphological studies have demonstrated tissue changes in patients with these lesions and tobacco substances. However, the effects of the tobacco components and the development of potentially malignant lesions remain unknown. Materials and Methods Thus, by chemical-biological analysis, we investigated compounds present in tobacco and the expression of genes involved in the etiopathogenesis of actinic cheilitis. Results and Discussion Analysis showed a ratio of 51 harmful substances present in tobacco that are involved in several biological processes that can cause abnormal epithelial-mesenchymal transition pathway. Also, describe how cadmium can adversely affect signaling and cell differentiation through the inhibition of specific proteins. Conclusion This study provides the first approach that describes how different tobacco constituents affect a vast network of biological processes in the development of actinic cheilitis and possible progression of the lip carcinoma.